Application of group positive psychotherapy to improve psychological well-being for people with HIV in Papua - Nasrah, Nasrah; Suweni, Korinus; Maay, Jems K. R.; Mohd Arifin, Siti Roshaidai; Yousuf, Abdilahi (Sanglah General Hospital, 2023)
Introduction: Problems that arise in a person with HIV/AIDS status are related to disease conditions and psychosocial conditions that can affect psychological well-being. One form of intervention that can improve psychological wellbeing is Group Positive Psychotherapy. The present study aimed to investigate the effect of implementing positive group psychotherapy in improving the psychological well-being of people living with HIV/AIDS (PLWHA) in the working area of the Timika Jaya Health Center, Mimika Regency. Method: This is a quasi-experimental research with the One Groups Pretest-Posttest Design technique approach. Respondents were pretested before the group positive psychotherapy treatment with counseling and education methods. Upon completing the treatment, a posttest was administered. The population of this study was the entire community of PLWHA in the working area of the Timika Jaya Public Health Center with 27 people for a total sampling technique. Data analysis used Chi-Square Test and Paired Samples T-Test. Based on the results of the analysis using paired sample t-test, p-value = 0.000 <α means that there is a significant difference in psychological well-being in PLWHA before and after 1 month of positive group psychotherapy intervention. Result: Furthermore, from 1 month of group positive psychotherapy intervention to the next 2 months, p = 0.000, and before the second group positive psychotherapy intervention, p = 0.000. Overall, there was a significant difference in the improvement of psychological well-being before and after the group positive psychotherapy intervention. Conclusion: Group positive psychotherapy effectively improves psychological well-being for people with HIV/AIDS.